Manajemen Laba dalam Sorotan Tax Avoidance: Moderasi Audit Pajak pada Perusahaan Subsektor Perkebunan Kelapa Sawit Indonesia - Rudiana Fibriani; Istiyanatul Mahbubah (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
The practice of tax avoidance is still a challenge in optimizing state revenues, especially in sectors that have operational complexity and global exposure, such as the oil palm plantation subsector. Flexibility in financial reporting through earnings management and supervision through tax audits are two factors that are thought to influence a company’s tax behavior. This research aims to examine the influence of earnings management on tax avoidance and the role of tax audit as a moderating variable in oil palm plantation subsector companies listed on the Indonesia Stock Exchange. This research uses a quantitative approach with secondary data in the form of annual financial reports. The sample was determined using a purposive sampling technique. Data analysis was carried out using the PLS-SEM method using SmartPLS 4.0. Earnings management is measured using discretionary accruals, tax avoidance using the cash effective tax rate (CETR), and tax audits using dummy variables. The research results show that earnings management has no effect on tax avoidance, while tax audits have a negative but not significant effect. However, tax audits have been proven to be able to moderate the influence of earnings management on tax avoidance. These findings indicate that fiscal monitoring plays a more important role in shaping the relationship between variables than as a direct factor. This research contributes to enriching the tax accounting literature, especially regarding the interaction between accounting policies and tax supervision mechanisms in the context of resource-based industries.